Estudio Psicológico y Psiquiátrico del filicidio como hecho punible que atenta contra la vida de los descendientes - Hurtado Rey, Ana Cristina (2023)
The present degree work entitled: "Psychological and Psychiatric Study of filicide as a punishable act that threatens the life of the descendants", since the research interest of this topic is due to the fact that it is evident that the state through the jurisdictional function does not comply with the rehabilitation of people through the internment in psychiatric hospitals as established in the criminal law, and it is proven that many of the people who are sentenced for committing the crime of filicide suffer from mental disorders which makes them unimputable. The study shows that filicide is a crime committed in most cases by parents who suffer from mental disorders such as psychosis in their different areas, this is the cause with the highest mortality rate, in this crime the right thing to do is to conduct a psychological and psychiatric investigation of the parents to determine their mental condition and establish their level of imputability and thus know if it is considered as a punishable act or not against the unimputability of the actor. In the present degree work the use and application of materials and methods that allowed the development of the same was made, for this purpose interviews were conducted with legal professionals, psychologists and forensic doctors whose results served to conclude that judges do not rule the internment in psychiatric hospitals for several reasons, such as the lack of free internment centers, lack of professionals and lack of research during the process.